Improving Cocoa sector Climate-Smart Awareness and decision-making - International Institute of Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security; Rainforest Alliance; Root Capital; Sustainable Food Lab (2018)
The cocoa sector recognizes climate change and weather volatility as direct threats to their businesses, and some are acting to incorporate climate smart practices into their programs in West Africa. This case study shares cocoa companies’ perceptions regarding the usefulness of the Climate Change, Agriculture and Food Security (CCAFS)-led Consortium’s research and onvening on climate smart cocoa (CSC) in Ghana, also in connection to the USAID Feed the Future Climate Smart Cocoa Program, led by the World Cocoa Foundation (WCF). While a large cross section of the industry has attended the CCAFS and CSC meetings and had access to the materials, this document focuses on four of the companies engaged. Included are company-specific case studies which describe how Touton, Ecom, The Hershey Company (Hershey), and Olam have leveraged the decision-support tools produced by CCAFS, namely climate suitability maps, the science underpinning the Climate Smart Cocoa Manual with recommendations by impact zone, and various climate-smart agriculture (CSA) Apps. We share also companies’ constructive feedback on remaining gaps and opportunities, and conclude with potential future directions for CCAFS and USAID for effective partnership with industry. The case was developed by the Sustainable Food Lab, in collaboration with IITA, in July-September 2018 and draws from extended qualitative interviews with four cocoa companies and several project participants.